Yoga and Physical Education: Its Impact on Wellbeing - K.V.S. NAIDU; M. VASUDEVA RAJU (Researchparks Publishing, 2022)
Yoga is a philosophical system from India that emphasises the importance of working with the body to develop healthy behaviours and thoughts. Physical postures, known as asanas in Sanskrit, are among the techniques learned. Athletics and gymnastics are part of the Physical Education programme, as you may recall. There was a time when people said,